Graft-versus-host disease in patients treated with allogenic hematopoetic cell transplantation: experience from North Macedonia - Mickovski, Ivana; Buklioska Ilievska, Daniela; Georgievski, Borche; Hasan, Taner; Nedeska Minova, Natasha; Neshovska, Radmila; Doneva, Daniela (VM Media SP. zo.o VM Group SK, 2021)
Introduction: Graft-versus-host disease (GvHD) is the major complication arising after allogeneic hematopoietic cell transplantation (allo-HCT). It can be presented as acute and/or chronic GvHD. The purpose of this study was describe the incidence of acute and chronic GvHD in patients treated with allo-HCT. Materials and methods: This study was designed as a retrospective study, which included 65 patients treated with allogeneic transplantation from human leukocyte antigen identical donor at University Clinic of Hematology in Skopje, North Macedonia. Results: Acute GvHD (aGvHD) was observed in 28 patients, with the most common localization on the skin (75%). Post-transplant phase had significant effect on the frequency of skin aGvHD (p =0.038). Also statistically significant difference was confirmed between patients with and without acute skin GvHD in terms of conditioning regimen (p =0.034). Chronic GvHD (cGvHD) was diagnosed in 10 patients, mostly progressing from the previous acute GvHD (9.23%). Post-transplant phase had also significant effect on the frequency of skin cGvHD (p =0.018). Patients with higher European Society for Blood and Marrow Transplantation risk score had significantly more frequent skin cGvHD than the others. Conclusions: Acute and chronic GvHD were one of the main causes of morbidity and mortality of patients after aloo-HCT. GvHD remains a major risk for patients with allo-HCT regardless of diagnosis and type of transplantation.
Keywords: allogeneic transplantation; acute and chronic GvHD; conditioning regimen; donor-recipient match; immune system